Time-dose response and mechanistic specificity of berberine in renal fibrosis from a multi-model integration perspective: a systematic review and meta-analysis on animal models - Nie, Ruyi; Yuan, Ziting; Wu, Yizhe; Pan, Minqi; Lu, Jiandong; Xiong, Guoliang (Frontiers in Pharmacology, 2025)
ObjectiveThis research intends to comprehensively evaluate the efficacy of berberine (BBR) and the specificity of its mechanisms of action in different animal models of renal fibrosis through a multi-model integration strategy.MethodsA comprehensive search of animal experimental studies was carried out across 10 different databases, including PubMed, Embase, Web of Science, Scopus, Cochrane Library, SCIELO, CNKI, Wanfang database, CBM and VIP Information Chinese Periodical Service Platform, spanning from their inception up to November 2024. The included studies’ methodological quality was assessed using the SYRCLE’s risk of bias tool for animal experiment, and statistical analyses were carried out with Stata 18.0.ResultsIn total, 26 animal studies (2010–2024) were included, encompassing diverse models of renal fibrosis. The Meta-analysis revealed that BBR significantly lowered serum creatinine, blood urea nitrogen, α-SMA, and TGF-β1 levels, alongside reductions in renal fibrosis area and oxidative stress markers. The time-dose response analysis indicated that BBR was most efficacious within the 100–400 mg/kg dose range over a 5–12-week intervention period. Still, the mechanism of action was model-dependent: in the UUO model, BBR predominantly modulated the AMPK/PPARα pathway and ferroptosis, while in the DN model, it primarily targeted glycolipid metabolism and epigenetic regulation.ConclusionBBR significantly ameliorates renal fibrosis progression through a multi-targeted mechanism that is model-specific. Although preclinical evidence supports its therapeutic potential, the interpretation of the conclusions requires caution, considering the significant heterogeneity and methodological quality differences among the included experiments.Systematic Review Registrationhttps://www.crd.york.ac.uk/, identifier CRD42024619202